OsRE1 interacts with OsRIP1 to regulate rice heading date by finely modulating Ehd1 expression. Issue 2 (28th August 2020) - Chai, Juntao; Zhu, Shanshan; Li, Chaonan; Wang, Chunming; Cai, Maohong; Zheng, Xiaoming; Zhou, Liang; Zhang, Huan; Sheng, Peike; Wu, Mingming; Jin, Xin; Cheng, Zhijun; et al.
Summary: Heading date is a key agronomic trait affecting crop yield. In rice, Early heading date 1 (Ehd1) is an important B‐type response regulator in determination of heading date. Although many regulatory factors of Ehd1 expression have been functionally characterized, the direct regulators of Ehd1 largely remain to be identified. Here, we identified a new regulator of Ehd1, OsRE1, that directly binds to the A‐box motif in the Ehd1 promoter. Osre1 confers an early heading phenotype due to elevated expression levels of Ehd1 . OsRE1 is a nucleus‐localized bZIP transcription factor with a diurnal rhythmic expression pattern. Furthermore, we identified an OsRE1‐interacting protein, OsRIP1, and demonstrated that OsRIP1 can repress the transcript expression of Ehd1 in an OsRE1‐dependent manner. Our genetic data showed that OsRE1 and OsRIP1 may function upstream of Ehd1 in regulating heading date. Together, our results suggest that OsRE1 functions cooperatively with OsRIP1 to regulate heading date through finely modulating the expression of Ehd1 . In addition, OsRE1 and OsRIP1 are two minor heading date regulators, which are more desirable for fine‐tuning heading date to improve rice regional adaptability.